Investigating Learning Questions Used in SMA Negeri 5 Kota Bukittinggi: A Cognitive Level Analysis - Gema Millenia Pani; Hamzah Hamzah (Universitas Negeri Padang, 2022)
This study aims to find out the distribution of cognitive levels on questions used for learning in SMA Negeri 5 Kota Bukittinggi. Additionally, the findings of LOTS and HOTS questions proposed for learning in SMA Negeri 5 Kota Bukittinggi are analyzed and then described. The analysis in this study is based on Revised Bloom’s Taxonomy. The informants of the research are 3 English Teachers who teach in grade X, XI and XII. To answer all questions, a descriptive research is conducted to describe the result of the research. The results of the study show that there are significant imbalances in the distribution of different level of questions during the learning process. In most cases, the teachers across all grades are more inclined to propose LOTS-based questions than its HOTS counterpart. Specifically, this research found that remembering (C1) and understanding (C2) level of questions dominated the distribution of questions in SMA Negeri 5 Bukittinggi with the combined overall percentage of more than 50%. Despite this, there was a pattern of increase in the percentage of HOTS questions as the grade increases. Grade XII shows higher percentage of HOTS-based questions compared to the other grades. However, the percentage of HOTS-based questions given in learning is found to be higher than LOTS questions.